Open Science in Africa – Challenges, Opportunities and Perspectives - Ahinon, Justin, Sègbédji; Havemann, Johanna (My University, 2018)
Open Science is becoming increasingly popular globally and provides unprecedented opportunities for scientists in Africa, South East Asia, and Latin America. African scientists face several difficulties when attempting to get their work published in peer reviewed journals -there is a small number of publication platforms, a lack of knowledge and access difficulties related to existing journals, whose visibility on the web is not very good (Piron et al., 2017). There are also obstacles related to the functioning of the journals themselves (notably the duration of the revision process and the cost of publications) and the result is that science and scholarly publishing are often perceived as a prerogative of the Northern countries. The methods and techniques (including the peer review process) that are being developed for its dissemination are not necessarily adapted to the contexts of other regions of the world, including Africa. Indeed, many African-based peer-reviewed scholarly journals are unable to host their content online due to resource limitations and the digital divide (Agaba et al., 2004). In this article, we provide an overview of the most important initiatives and actors in the Open Science movement in Africa. We further identify three major challenges for Open Science on the African continent and offer perspectives for African researchers to actively contribute to the global scientific community and share knowledge to meet the challenges we all face.
Supplemental Materials: https://osf.io/3azsh/
Keywords: Open Access; Open Hardware; Open Science; Science in Africa